The influence of trustworthiness and technology acceptance factors on the usage of e-government services during COVID-19: A case study of post COVID-19 Greece - Stefanos Balaskas; Aliki Panagiotarou; Maria Rigou (Administrative Sciences, 2022)
The COVID-19 pandemic imposed challenges and offered opportunities, which were recognized and assessed in developed countries. In many cases though, the lack of systematic preparation for the required digital transformation resulted in confusion and discomfort in citizens' lives, where the imposition of nonphysical contact excluded a large part of the population from basic needs and rights. This article investigates the influence of trustworthiness and technology acceptance factors on the usage of e-government services during the pandemic, and proposes a model that integrates factors adapted from the TAM model (social influence, performance expectancy and effort expectancy) with trust in e-government, a factor influenced by trust in government, trust in the internet, security and privacy, to predict e-government usage. To test the model, a survey was conducted using a 38-question questionnaire we designed, with a total sample size of 301 Greek citizens. The model was confirmed using the structural equation modeling (SEM) approach with maximum-likelihood estimates. Results indicate that all aspects in this study related to trustworthiness and user acceptance can be predictive factors of citizens' usage of e-government services during periods of uncertainty and high risk, such as the COVID-19 pandemic.
Keywords: 350; citizen engagement; COVID-19; e-government services; Greece; technology acceptance model (TAM); trustworthiness; user acceptance